2013
DOI: 10.3892/br.2013.53
|View full text |Cite
|
Sign up to set email alerts
|

β-2 microglobulin is unsuitable as an internal reference gene for the analysis of gene expression in human colorectal cancer

Abstract: Abstract. It is well-known that gene expression levels should be normalized to a carefully selected and appropriately stable internal control gene. However, numerous studies have demonstrated that the expression of housekeeping (HK) genes, typically used as internal control genes varies considerably. A number of studies have shown that β-2 microglobulin (B2M), an HK gene, frequently used as an internal reference gene, is expressed at low levels in colorectal cancer tissue, when assessed using real-time reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…b2mg is a component of MHC class I molecules, which are present on all nucleated cells and it has been found to be a suitable reference gene in mouse hematopoetic stem cells [ 31 ], and in K562 cells and leucocytes of normal individuals as well as of malignoma patients [ 32 ] and different tissues of Japanese flounder ( Paralichthys olivaceus ) [ 33 ]. However, in some other studies involving human colorectal cancer cells [ 34 ] and human reticulocyte cells [ 19 ] it has been reported not to be a suitable reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…b2mg is a component of MHC class I molecules, which are present on all nucleated cells and it has been found to be a suitable reference gene in mouse hematopoetic stem cells [ 31 ], and in K562 cells and leucocytes of normal individuals as well as of malignoma patients [ 32 ] and different tissues of Japanese flounder ( Paralichthys olivaceus ) [ 33 ]. However, in some other studies involving human colorectal cancer cells [ 34 ] and human reticulocyte cells [ 19 ] it has been reported not to be a suitable reference gene.…”
Section: Discussionmentioning
confidence: 99%
“…Both plasma and urinary B2M levels may be reliably and cost-effectively measured [194]. Although it has also been used as a housekeeping or reference gene in exercise and nutrition interventions [195,196], researchers should consider that B2M might be unsuitable for some conditions [197,198]. It has been demonstrated that reduction in the intestinal HEPH and CP-ferroxidase activity may impair Fe absorption and Fe release from intracellular stores, respectively, which decreases Fe levels and results in disturbances of Fe delivery in the bone marrow to support erythropoiesis [199].…”
Section: Evidence-based Verification Of the Identified Potential Biom...mentioning
confidence: 99%